(untitled) (Journal of Partial Differential Equations, 1989)
Let M be a complete Riemannian manifold, and let &#916 be the Laplacian on M. ln this paper, we study the global properties of positive solutions of &#916U + b &#8226 &#8711U + hU^&#945 = 0 We mainly prove some theorems of Liouville type.